If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(v + -4) + -8v = -20 Reorder the terms: 6(-4 + v) + -8v = -20 (-4 * 6 + v * 6) + -8v = -20 (-24 + 6v) + -8v = -20 Combine like terms: 6v + -8v = -2v -24 + -2v = -20 Solving -24 + -2v = -20 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '24' to each side of the equation. -24 + 24 + -2v = -20 + 24 Combine like terms: -24 + 24 = 0 0 + -2v = -20 + 24 -2v = -20 + 24 Combine like terms: -20 + 24 = 4 -2v = 4 Divide each side by '-2'. v = -2 Simplifying v = -2
| 2y+6(y+2)=-36 | | x=5-1/x | | 0.2x-0.4(5-x)=0.7 | | x*x-23=52-2*x*x | | 5m-4=41 | | 1/x=5-x | | 8(w-4)-5w=-17 | | 18-2x=(x-9) | | 2x+4+8x-8=180 | | ln(13/x) | | -10(s+3)=-21 | | 5x+x=510 | | -5x+xy=4 | | 2/3n=8/15 | | -(c-8)=-21 | | -4(x+2)+3=6(x+2)+2 | | x+10x+100x=11100 | | 10x+3=5x+47 | | -4v-10=46 | | 24/8=n/17 | | -7-z=-2z | | 20=2/3g | | (2-3x)(4x+5)=0 | | 7x+27=9x-7 | | 4(x+2)-10=2(x+3) | | K/9=99 | | 5+4p=6p-9 | | 8X=32/3 | | -2(6n-7n)+5n=145 | | 5(3s+8)=180 | | -4-6v=10-4r | | -3*a-6=24 |